Arabic Language Skills Development Through The Application Of Language Disciplines In Modern Islamic Boarding Schools/ تطوير مهارات اللغة العربية وجعلها نظاما للتواصل في المعهد الإسلامي العصري - Malkan, Mardhiya Agustina; Jannah, Wardhatul; Jamhuri, Rif'ah Kasyfuddin (UIN ANTASARI, 2022)
The study was conducted in order to describe the students’ Arabic language skills development process at Pondok Modern (Modern Islamic Boarding School) An-Najah, South Kalimantan. Arabic language skills at PM An-Najah are developed by applying the language discipline method. This process combines the provision of material in the classroom and the application of language discipline in both of the classroom and the dormitory environment. One of the competency standards for graduates of PM An-Najah is that students are capable to demonstrate Arabic language skills, such as istima (listening), kalam (speaking), qira'ah (reading) and kitabah (writing), at the intermediate level. This research was conducted by means of qualitative methods with field research as the specification. The data were collected through interviews, observations and documentation studies, and then were analyzed and presented descriptively. The result of the study indicated that: (1) the process of applying language discipline was carried out through several stages, namely (a) language programs planning, (b) socialization, (c) habituation, (d) adaptation, (e) raising awareness, and (f) mastery of language skills; (2) the determining factors for the development of students' language skills include (a) system and environment, (b) educators, (c) discipline, and (d) the students themselves; and (3) the supporting factors for the development of students' language skills consist of (a) direction and guidance, (b) cooperation, and (c) infrastructure.